Exosomal miR-500 Derived From Lipopolysaccharide-Treated Macrophage Accelerates Liver Fibrosis by Suppressing MFN2 - Chen, Lisha; Huang, Yan; Duan, Zhixi; Huang, Peiqi; Yao, Hongbing; Zhou, Yu; Ji, Qin; Liu, Xiangfeng (Frontiers in Cell and Developmental Biology, 2021)
Liver fibrosis is an outcome of chronic hepatic injury, which can eventually result in cirrhosis, liver failure, and even liver cancer. The activation of hepatic stellate cell (HSC) is a prominent driver of liver fibrosis. Recently, it has been found that the crosstalk between HSCs and immune cells, including hepatic macrophages, plays an important role in the initiation and development of liver fibrosis. As a vital vehicle of intercellular communication, exosomes transfer specific cargos into HSCs from macrophages. Here, we show that exosomes derived from lipopolysaccharide (LPS)-treated macrophages has higher expression level of miR-500. And overexpression or inhibition of miR-500 in macrophage exosomes could promote or suppress HSC proliferation and activation. Treatment of exosomes with miR-500 overexpression can accelerate liver fibrosis in CCl4-induced liver fibrosis mouse model. miR-500 promotes HSC activation and liver fibrosis via suppressing MFN2. Moreover, miR-500 in serum exosomes could be a biomarker for liver fibrosis. Taken together, exosomal miR-500 derived from LPS-activated macrophages promotes HSC proliferation and activation by targeting MFN2 in liver fibrosis.